Juridical Overview of Loan-Lending Agreements that are Declared Void by Law - Muhammad Nur Ukasyah (Arkus, 2020)
This study aims to determine whether the decision of West Jakarta District Court which decided Loan Agreement between Nine AM Ltd. with PT. Bangun Karya Pratama Lestari is null and void according to the law of treaties or not and to know the legal implications of the West Jakarta District Court decision in Case Number 451 / Pdt.G / 2012 / PN.Jkt.Bar about the cancellation of loan agreements. This research using normative legal research by the statute approach and a case approach. The results of this study were 1) the West Jakarta District Court decision was in accordance with the law of treaties that the agreement is null and void. This decision caused by the Loan Agreement was infringing Article 1320 of the Burgerlijk Wetboek, that is not the fulfillment of the elements of a cause of the lawful and contrary to Article 31 of Act number 24 of 2009 concerning Flag, Language, and The State Emblem and Anthem Language and Article 1339 of the Burgerlijk Wetboek which provides that an agreement is not only bound to what is explicitly approved in the agreement, but also bound by propriety, customs, and laws. 2) Juridical implications of that decision is any agreement that is not made in accordance with the provisions of Article 31 Act number 24 of 2009 concerning Flag, Language, and The State Emblem and Anthem will be declared null and void / agreement is deemed never existed and the parties returned in original condition. Likewise with any follow-up agreement (assumed as accessories) will be declared null and void anyway, even the agreement made with the competent authority knowing it.